Форми реалізації концептуальної моделі носіїв науково-популярного контенту - Петрушка, Аліна (Видавництво Львівської політехніки, 2017)
The article is devoted to the problems of creating a conceptual model of the science and popular content carriers based on foresight methodology. The features of determining the structure and presentation of relationships between the model’s constituent elements in tabular and graphical form are given.
Keywords: модель; контент; мас-медіа; стратегічне проектування; концепція